إكثار نبات الستيفيا Stevia rebaudiana بوساطة زراعة الأنسجة النباتية - محسن وسيم; القنطار خزامة; زيد سليم; عبد القادر أحمد (Latakia University Journal -Biological Sciences Series, 2019)
أوضحت التجارب أن المعاملة رقم 5 المحتوية على: MS+ 4.44mM BA+ 1.07 mM NAA، أعطت أفضل النتائج من حيث متوسط عدد النموات الخضرية الجديدة المتشكلة/ خزعة (4.9 نمو) ومتوسط عدد الأوراق/نمو (20.5 ورقة) مقارنة بباقي المعاملات, بينما كانت المعاملة رقم 8 المحتوية على: MS+ 4.64 mM Kin+ 1.07 mM NAA+ 0.58 mM GA3 ، الأفضل لجهة متوسط طول النموات الخضرية (3.5 سم) . نقلت النموات الحديثة بطول 2-3 سم إلى أوساط تجذير مختلفة شملت: (MS, 1/2MS, MS+2.46 or 4.92 mM IBA)، حيث أظهرت النتائج أن نسبة التجذير الأعلى كانت 100 % وعدد الجذور المتشكلة 15.7 جذر/نبات في الوسط المحتوي على4.92 mM IBA . نقلت النباتات المجذرة إلى أوعية تحتوي خليط بنسبة 2/1 من تورب/ برليت من أجل عملية الأقلمة التي تمت تدريجيا خلال مدة 2-4 أسابيع وبلغت نسبة نجاح التقسية 89.4%. The results have shown that MS medium containing: 4.44 mM BA + 1.07 mM NAA had the best effect on number of new shoots formed with average of 4.9 per explant, while medium containing: MS+ 4.64 mM Kin. + 1.07 mM NAA and 0.58 mM GA3 had the best effect on average shoots length (3.5 cm). 2-3 cm length proliferating shoots were transferred into different rooting media (MS, 1/2MS, with 2.46 mM or 4.92 mM IBA) with a maximum efficiency of 100% rooting with average of 15.7 roots per rooted plantlet obtained in case of MS medium with 4.92 mM IBA. Rooted plantlets were transplanted into pots with a mixture of 2:1 (v/v) peat/perlite for acclimatization gradually to field conditions within 2-4 weeks. Acclimatization percentage was 89.4%.